Utilização de melaço, manipueira e soro de queijo como substratos para produção de biossurfactante por Bacillus Pumilus e sua aplicação em biorremediação de solo - Oliveira, Juliana Guerra de [UNESP] (2014)
Surfactants are molecules that contain hydrophilic and hydrophobic moieties, and because of this, they are capable of reducing the surface tension of a medium containing water. This feature is important for industrial applications by making these surface active compounds of high interest. On the other hand, biosurfactants are molecules that exhibit surfactant characteristics and are produced by microorganisms. They have large surface- active power and the advantage of being produced from renewable substrates; in addition to being biodegradable, have low toxicity and chemical specificity. The objective of the work was to investigate the production of a biosurfactant by Bacillus pumilus using cassava, molasses, cheese whey and sucrose as substrates; check the production and properties of this biosurfactant on a large scale (2L) using sucrose as carbon source, as well, as their potential for application in bioremediation of an agricultural soil contaminated by hydrocarbons. All experiments were planned using surface response methodology. For all fermentation experiments the emulsification index, surface tension, and microbial growth analyses were performed. In all substrates tested, the crude concentration and the stability of the biosurfactant produced were determined in extremes conditions of temperature, pH and salinity. The results showed that the bacterium Bacillus pumilus was able to grow and produce biosurfactant with all substrates tested, reducing the surface tension to 46, 37, 47 and 32 mNm-1 with cassava, molasses, whey and sucrose, respectively. The biosurfactant was able to present emulsification rates of up to 50% with toluene and soybean oil. The crude production obtained was (g/L): 1.12; 0.35, 1.4 and 5.1 for cassava, molasses, whey and sucrose, respectively. The biopolymer produced was stable across variations in temperature, pH and salinity. In the large-scale fermentation with sucrose ...